2019
DOI: 10.3390/rs11080904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Water Scarcity in Africa Using GRACE and TRMM Satellite Data

Abstract: The critical role of water in enabling or constraining human well-being and socioeconomic activities has led to an interest in quantitatively establishing the status of water (in)sufficiency over space and time. Falkenmark introduced the first widely accepted measure of water status, the Water Scarcity Index (WSI), which expressed the status of the availability of water resources in terms of vulnerability, stress, and scarcity. Since then, numerous indicators have been introduced, but nearly all adopt the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Keen attention must be paid to areas that are more affected by water scarcity, such as the African continent [324,325], where water shortages may concern 37% of the 2025 population (~600 million people) and 57% in 2050 (~1.4 billion people), under the hypothesis of a decrease in water resources by 10%. Concerning water management, Biswas and Tortajada [326] point out unambiguously that "countries will have to manage their water significantly better, because they will have no other choice".…”
Section: Discussionmentioning
confidence: 99%
“…Keen attention must be paid to areas that are more affected by water scarcity, such as the African continent [324,325], where water shortages may concern 37% of the 2025 population (~600 million people) and 57% in 2050 (~1.4 billion people), under the hypothesis of a decrease in water resources by 10%. Concerning water management, Biswas and Tortajada [326] point out unambiguously that "countries will have to manage their water significantly better, because they will have no other choice".…”
Section: Discussionmentioning
confidence: 99%
“…Then a fixed sample grid to GRACE CSR-M product was used to sample the corresponding trend value at a fixed spatial resolution of 1.0-degree grid. The associated uncertainty in each variable was expressed using standard deviations of the residual component following standardized approaches [7,39,69,79,80]. Table 1.…”
Section: Nile River Basinmentioning
confidence: 99%
“…TWSA, and several independent variables can be analyzed based on either the raw values of the process or on the dominant component characterizing the time series, such as trends, cycles, and seasonality [59,[81][82][83][84][85]. With specific respect to TWSA across Africa, previous research (e.g., [7,16,18,19,24,25,35,38,86]) showed that large parts of the continent are experiencing statistically significant declining TWSA trends. The studies further established that the trend component provides a robust means of investigating the relationship between TWSA and the driving hydrologic variables.…”
Section: Trend Analysismentioning
confidence: 99%
See 2 more Smart Citations